Analysis of Agile Practices Adoption on CMMI Organizations through a Systematic Literature Review - Marco Palomino; Abraham Dávila; Karin Melendez; Marcelo Pessoa (ReCIBE)
In the recent years, the adoption of agile frameworks and methodologies in Software Development Organizations (SDO) has grown up considerably. Unfortunately, the level required of formal documentation in bigger or longer software development projects is not full covered by agile practices alone; likewise, this kind of situations happen frequently in a context of CMMI organizations. The aim of this study is identify, review and analyze the most used agile practices that are being used in combination with CMMI within SDO. To accomplish this, a systematic literature review has been performed according to relevant guidelines. This study has identified multiple practices such as Daily Meeting and Product Backlog management that are being used constantly in combination with CMMI. In addition, we could identify that there are specific benefits of implementing practices from both approaches.